Effects of duration of electric pulse on in vitro development of cloned cat embryos with human artificial chromosome vector. (28th August 2016) - Do, LTK; Wittayarat, M; Terazono, T; Sato, Y; Taniguchi, M; Tanihara, F; Takemoto, T; Kazuki, Y; Kazuki, K; Oshimura, M; Otoi, T
Contents: The current applications for cat cloning include production of models for the study of human and animal diseases. This study was conducted to investigate the optimal fusion protocol on in vitro development of transgenic cloned cat embryos by comparing duration of electric pulse. Cat fibroblast cells containing a human artificial chromosome (HAC) vector were used as genetically modified nuclear donor cells. Couplets were fused and activated simultaneously with a single DC pulse of 3.0 kV/cm for either 30 or 60 μs. Low rates of fusion and embryo development to the blastocyst stage were observed in the reconstructed HAC‐transchromosomic embryos, when the duration of fusion was prolonged to 60 μs. In contrast, the prolongation of electric pulse duration improved the embryo development and quality in the reconstructed control embryos without HAC vector. Our results suggested that the optimal parameters of electric pulses for fusion in cat somatic cell nuclear transfer vary among the types used for donor cells.